2021
DOI: 10.3855/jidc.13091
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Gardnerella vaginalis, Atopobium vaginae and Lactobacillus spp. in bacterial vaginosis

Abstract: Introduction: The aim of the study was to investigate prevalence of bacteria most frequently associated with bacterial vaginosis using Amsel’s criteria as well as to quantify these bacteria by real-time PCR and to explore the difference in their quantity between healthy and bacterial vaginosis samples. Methodology: For classification of vaginal discharge samples Amsel’s criteria have been used. To detect and quantify Gardnerella vaginalis Atopobium vaginae, Lactobacillus spp. and total vaginal microbiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Others have reported that the relative abundance of pretreatment Lactobacillus, or the ratio of Gardnerella to Lactobacillus 16S DNA [67,103] or RNA [104], was associated with clinical outcome. Neither of these associations were significant in our cohort, nor in our larger cohort analyzed by qPCR [15]; abundance of total Lactobacillus spp or L. iners at pretreatment or among Amsel-negative posttreatment patients was not prognostic of clinical outcome.…”
Section: Plos Onementioning
confidence: 99%
“…Others have reported that the relative abundance of pretreatment Lactobacillus, or the ratio of Gardnerella to Lactobacillus 16S DNA [67,103] or RNA [104], was associated with clinical outcome. Neither of these associations were significant in our cohort, nor in our larger cohort analyzed by qPCR [15]; abundance of total Lactobacillus spp or L. iners at pretreatment or among Amsel-negative posttreatment patients was not prognostic of clinical outcome.…”
Section: Plos Onementioning
confidence: 99%
“…Our result is controversial since different authors have linked a potential impact of GV in the development of cervical lesions and/or cancer while others fail to show any association 68,71–73 . Furthermore, some authors have been showing that quantification of some microorganisms such as GV may be of potential interest, which should be further explored 74 …”
Section: Discussionmentioning
confidence: 70%
“…68,[71][72][73] Furthermore, some authors have been showing that quantification of some microorganisms such as GV may be of potential interest, which should be further explored. 74 Regarding other common agents, we found that MH (p = 0.028; RR = 1.51) and Mob were highly associated with HPV-9val (p = 0.025; RR = 1.85). Nevertheless, Mob showed to be associated with protection against the development of any cervical lesion (p = 0.022; OR = 0.29).…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, infections with sexually transmitted bacteria and bacterial vaginosis can find an excellent niche for implantation. Gardnerella vaginalis and Atopobium vaginae have been considered markers of abnormal vaginal microbiota [4], as they actively contribute to the generation of an unstable microenvironment [5,6]. Moreover, increased microbial diversity is also associated with viral persistence and progression to cervical cancer in oncogenic human papillomavirus (HPV) infections [7].…”
Section: Introductionmentioning
confidence: 99%